Nationalism or quest for justice? : a case study of the Patani-Malay uprisings (1909-2009) - Wan Mohamad Marzuqi Bin Wan Hashim (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
This thesis attempts at discovering the recent cause of uprisings in Patani, beginning in 2004, i.e. three years after the Thaksin-led government came to power in Thailand. The majority of studies on Southern Thailand tend to point out that Malay nationalism has been the key factor leading to the emergence of the Malay-speaking Muslim uprisings in the region for the last forty years. There is a question on why the Malay-speaking Muslims decided to halt their armed struggle against the central government in the 1980s if nationalism was the main cause of the uprisings. It was reported that the Patani region experienced peace and stability for almost two decades until 2001 when Thaksin Shinawatra won the general election and became Prime Minister. This thesis relies heavily upon primary materials such as texts, unpublished works, dissertations, theses, documents, periodicals, leaflets, propaganda literatures, and newspaper reports found at various universities in Malaysia and Thailand. Apart from that, it also relies upon interviews with several political and community figures in the two countries as well as other external observers. This thesis discovers that all the violent incidents that have been occurring in the region are not merely caused by the Patani liberation movements as many media claim. Instead, there have been invisible hands which play their roles for certain purposes. Some government security forces, especially the military officers and members of the government paramilitary groups, are believed to have been involved in violent incidents as a result of their dissatisfaction of the Thaksin-led government's policy against illicit businesses they have been carried out for decades. Attacks on government officials, buildings as well as civilians are believed to have two motives, first, to challenge the power of the Bangkok-based Royal Thai Police which the central government purposely brought to the Patani region, and second, to alert the military to the growing influence of the newly deployed Royal Thai Police in the region, suggesting that the police might take over all positions the military officers have been enjoying since the 1980s. As for the Patani liberation movements which have not involved in the violence since the conclusion of the peace treaty with Bangkok, they believe that the central government is not sincere in maintaining peace in the region. The liberation movements claim that the government security forces are conducting atrocities on the Malay-speaking Muslims systematically, thereby forcing them to retaliate.